Abolitionism and Regional Division in the United States before the Civil War - qizi , Yavkacheva Mokhlaroyim Azizbek; M. I., Gadoyeva (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This article explores the role of abolitionism in shaping and intensifying regional divisions between the Northern and Southern United States in the decades preceding the American Civil War. The abolitionist movement is examined as a powerful ideological force that exposed fundamental contradictions within American society, particularly between democratic ideals and the institution of slavery. Rather than functioning as a unifying reform movement, abolitionism contributed to the formation of sharply opposed regional identities rooted in divergent economic interests, social structures, and moral worldviews. In the Northern states, abolitionism gained prominence through moral discourse that emphasized human equality, religious ethics, and the incompatibility of slavery with republican values. These ideas were widely disseminated through literature, journalism, and public debate, shaping popular attitudes toward slavery and reinforcing a growing sense of moral opposition to the Southern social order. In contrast, the Southern states developed a defensive ideological framework that justified slavery as a necessary and legitimate institution, closely tied to regional prosperity and social stability. Southern cultural and literary narratives often portrayed abolitionism as a radical threat to social harmony and political autonomy. The article demonstrates that literature played a crucial role in this process by articulating and reinforcing competing interpretations of slavery and freedom. Abolitionist texts exposed the violence and injustice of slavery, while pro-slavery writings constructed idealized representations of plantation life and racial hierarchy. These conflicting narratives did not merely reflect existing tensions but actively contributed to the deepening of sectional polarization. By examining abolitionism within a broader cultural and historical context, the article highlights the significance of literary discourse in shaping political consciousness and regional division. The study underscores the importance of abolitionist and anti-abolitionist literature as a valuable source for understanding the ideological foundations of the Civil War and the cultural dynamics of nineteenth-century American society.